2017
DOI: 10.1108/yc-06-2017-00705
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of personal factors in influencing the buying behavior of consumers in sales promotion: a case of fashion industry

Abstract: Purpose This study aims to investigate the influence of personal factors on the buying behavior of consumers with the intentions of sales promotion in the fashion industry. Precisely, it focuses on the marketing techniques and practices in sales promotion activities to influence the buying intentions of consumers in personal ways. Design/methodology/approach Based on a comprehensive literature review of personal factors, sales promotion and buying behavior, this study has applied a positivist approach to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 47 publications
(38 reference statements)
2
40
0
3
Order By: Relevance
“…And even farther, 45% respondents are agree and 25% are very agree that consumer make purchases at Dropbox Resto & Café is influenced by occupation. This is in accordance with the results of [15] indicating that personal factors have positive and statistically significant effects on the buying behavior of consumers in the fashion clothing industry of Pakistan.…”
Section: Fig 5 Developments and Modern Advance That Influen Decisiosupporting
confidence: 92%
“…And even farther, 45% respondents are agree and 25% are very agree that consumer make purchases at Dropbox Resto & Café is influenced by occupation. This is in accordance with the results of [15] indicating that personal factors have positive and statistically significant effects on the buying behavior of consumers in the fashion clothing industry of Pakistan.…”
Section: Fig 5 Developments and Modern Advance That Influen Decisiosupporting
confidence: 92%
“…Moreover, men are guided with one purpose; shop for the intended items and leave a store while women take time to scan the store as they maximize their shopping experience. Similarly, the findings of a study by Rehman, Yusoff, Zabri, and Ismail (2017) revealed the implication of personal factors as evidenced on shoppers' buying behaviour in the fashion industry. As an integral component in the shopping experience, malls have adopted marketing techniques that enable them to match the personal characteristics of shoppers -for example, interactions with sales attendants in a shopping mall elicits different reactions from men and women.…”
Section: Personal Attributesmentioning
confidence: 81%
“…It concludes that females spent significantly more time at shopping malls compared to males (p-value <0.001) ( Table 5). Gohary and Hanzaee (2014) and Rehman et al (2017) attributed factors that differentiate men's shopping habits to those manifested by women. There were 14.3% male and 4.4% female respondents who spent less than one hour in a mall whereas 22.5% female and 17.6% male respondents spent more than four hours.…”
Section: Gender Difference In Factors Affecting Buying Decisionsmentioning
confidence: 99%
“…Many researchers (e.g. Rehman, Yusoff, Zabri and Ismail 2017, Rani 2014, Lichev 2017, Martins, Yusuf, & Swanson 2011, Cranfield, Henson and Blandon 2012, Ostrovskiy, Garkavenko and Rybina 2019 focus on the influence of psychological and sociodemographic variables on customers' purchasing behaviour, as they play an important role in purchasing decisions. Khaniwale (2015), as well as Sukdeo (2018) and Yakup and Jablonsk (2012), suggest that is necessary to take into account personal characteristic of the customer since each customer as an individual is unique by personal characteristics and nature.…”
Section: Introductionmentioning
confidence: 99%